UPAYA PENINGKATAN KETERAMPILAN BERBICARA SISWA PADA MATA PELAJARAN BAHASA ARAB MELALUI LATIHAN KOMUNIKATIF DI MTSN PANINJAUAN KABUPATEN TANAH DATAR - Suharmon Suharmon (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2009)
This research was based on the needs of improving students’ speaking skill and teachers’ creativity in managing learning process on speaking skill at MTsN as a response to the lack of students’ speaking ability. This research, therefore, employed qualitative approach and analyzed by means of reflective, participative and collaborative studies. The setting of the research was MTsN Paninjauan by employing 2 cycles, each of which consisted of 4 meetings. In cycle 1, the students were not familiar with learning condition where communicative practices were applied and therefore were explained to them the principles so that the students and teachers got more familiar with. Observing on the students’ speaking it was found that students’ average improvement was 1.14 with average achievement was 48.1%. At the end of cycle 2, students’ speaking skill showed an average improvement of 3.9 with average percentage of achievement 79%.Kata Kunci : keterampilan , berbicara, teknik komunikatif, pemahaman, ujaran